THE ACT OF JIHAD ON HIGHER EDUCATION INSTITUTION AGAINST CORRUPTION - Abdul Wahid; Siti Marwiyah; Sunardi Sunardi (International Journal Education Multicultural of Islamic Society, 2021)
There is a paradoxical condition which afflicts higher education institution. On the one hand, higher education institution has proven itself as an educational institution which generates several knowledgeable and great people for the interest of Indonesian society and global community. However, another side of university is considered being affected by serious problems in relation with corruption in the state. Lots of notorious corruptors have already corrupted trillions of rupiahs from the state’s assets whereas these corruptors are higher education institution graduates. Moreover, there are many higher education institution elites who deal with law enforcement officials because they are alleged of doing corruption. A number of educational subjects in higher education institution were arrested by the Corruption Eradication Commission (KPK) because of their findings which indicate the misuse of government funds. Not only has it been regarded to physical construction of the higher education institution, but also the procurement of goods and services. Due to this condition, time has come for universities to promote educational jihad for the sake of corruption eradication in higher education institution.Keywords:  universities, corruption, educational jihad, eradication